KONSEP PENDIDIKAN SOSIO-PROGRESIF (Telaah Pemikiran Pendidikan Ibnu Khaldun) - Mubarak Mubarak (AZKIYA, 2018)
This study aims to describe Ibn Khaldun's view of socio-progressive education. Research data is collected through written documents in the form of printed books, journals, articles, etc. using descriptive content analysis techniques, which describe in detail the contents of the message or text by describing it in full. This study shows the results that Ibn Khaldun's socio-progressive education can be identified through the following views: (1) Science and teaching are natural in human beings, (2) The purpose of education is to fulfill religious needs, life needs and become a part from the Community, (3) Educators are individuals or communities who understand, are gentle and communicative towards students, (4) Students as subjects of education, and (5) Curriculum education is dynamic which emphasizes â€œmalakahâ€ in thinking and working for the progress of society.